The epigenetic regulator PLZF represses L1 retrotransposition in germ and progenitor cells. (31st May 2013) - Puszyk, William; Down, Thomas; Grimwade, David; Chomienne, Christine; Oakey, Rebecca J; Solomon, Ellen; Guidez, Fabien
<x xml:space="preserve">Abstract</x> Germ cells and adult stem cells maintain tissue homeostasis through a finely tuned program of responses to both physiological and stress‐related signals. PLZF (Promyelocytic Leukemia Zinc Finger protein), a member of the POK family of transcription factors, acts as an epigenetic regulator of stem cell maintenance in germ cells and haematopoietic stem cells. We identified L1 retrotransposons as the primary targets of PLZF. PLZF‐mediated DNA methylation induces silencing of the full‐length L1 gene and inhibits L1 retrotransposition. Furthermore, PLZF causes the formation of barrier‐type boundaries by acting on inserted truncated L1 sequences in protein coding genes. Cell stress releases PLZF‐mediated repression, resulting in L1 activation/retrotransposition and impaired spermatogenesis and myelopoiesis. These results reveal a novel mechanism of action by which, PLZF represses retrotransposons, safeguarding normal progenitor homeostasis.